2004
DOI: 10.1093/ajcn/79.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated linoleic acid on body composition and plasma lipids in humans: an overview of the literature

Abstract: Studies in mice have indicated that feeding diets containing 0.5-1% conjugated linoleic acid (CLA) considerably reduces body fat. These findings have attracted much interest because of the potential use of CLA as a tool to promote weight loss in humans. Several CLA studies in humans have now been published, and the objective of the present review was to give an overview of these experiments. Most of the studies were done in free-living subjects and were not strictly controlled for nutrient and energy intakes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(128 citation statements)
references
References 73 publications
4
116
0
8
Order By: Relevance
“…25 In humans, however, the majority of studies have shown that supplementation with CLA mixtures does not have an effect on plasma cholesterol or TG levels compared to controls. 5 Similarly, we found no difference between groups in the change in total cholesterol, LDL, HDL or TGs. We also assessed the effect of CLA on biomarkers of inflammation and endothelial dysfunction that have been linked to the development of cardiovascular disease: CRP, IL-6 and TNFR-2 are markers of systemic inflammation, whereas E-selectin, sICAM-1 and s-VCAM-1 are overexpressed in the presence of inflammatory stimuli to the endothelium.…”
mentioning
confidence: 44%
See 1 more Smart Citation
“…25 In humans, however, the majority of studies have shown that supplementation with CLA mixtures does not have an effect on plasma cholesterol or TG levels compared to controls. 5 Similarly, we found no difference between groups in the change in total cholesterol, LDL, HDL or TGs. We also assessed the effect of CLA on biomarkers of inflammation and endothelial dysfunction that have been linked to the development of cardiovascular disease: CRP, IL-6 and TNFR-2 are markers of systemic inflammation, whereas E-selectin, sICAM-1 and s-VCAM-1 are overexpressed in the presence of inflammatory stimuli to the endothelium.…”
mentioning
confidence: 44%
“…4 CLA's effect on body fat was first demonstrated almost a decade ago in mice, and research has since confirmed and extended these findings to include several species, with some variation by animal type and CLA isomer. 5 By far, the most dramatic results have been shown in mice with decreases in body fat between 40 and 80% compared to controls. 6 Proposed mechanisms have included increased fat mobilization and oxidation, reduced adipocyte proliferation and differentiation, and increased apoptosis in pre-adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies report contradicting results. Although in the majority of them there are no significant differences on body weight, body composition 26 or weight regain 27,28 between controls and CLA-supplemented groups, some studies suggest that CLA might have a tendency to increase lean body mass 27,29,30 . On one hand, one study carried out in overweight/obese adult volunteers 30 report a reduction in body fat mass with doses $3.4 g MI-CLA per day at week 12 (150-580 g more than placebo), with a significant increase in body lean mass in the group that received 6.8 g MI-CLA per day, measured by dual-energy X-ray absorptiometry; however, this group was also the only one with a significant increase in exercise level.…”
Section: Evidence Of Conjugated Linoleic Acid Effects On Body Weight mentioning
confidence: 99%
“…Today a number of beneficial physiological properties are attributed to CLA such as anti-cancer, anti-atherosclerosis, anti-inflammatory, and anti-obesity effects (reviewed in Scimeca 1999;Gnädig et al 2001;Pariza et al 2001;Evans ME et al 2002;Belury 2002;Terpstra 2004;Wahle et al 2004;Zulet et al 2005; Kelley et al 2007;Li et al 2008). These beneficial effects seem to be structure-specific.…”
Section: Introductionmentioning
confidence: 99%